Analysis of Environmental Criteria in Sustainability Reports of Companies in the Textile and Apparel Sector - Špela Kumer; Gregor Radonjič (Tekstilec, 2021)
The textile industry is often criticized for its enormous negative impact on the environment and non-human working conditions, especially in third-world countries. One of the goals of sustainability measures is the transparency of communications regarding environmental impacts and the policy measures of companies. So-called sustainability reports have become one of the most popular ways to communicate with stakeholders regarding the sustainability efforts of companies. In this paper, we analysed the content of the sustainability reports of textile industry and apparel companies with an emphasis on environmental criteria. We focused on the number of environmental criteria and analysed the measures taken in a given period. The results revealed that, in all cases, more detailed information regarding the carbon and water footprint were reported every year. In general, companies reported the most about measures taken in the production and raw material extraction phases, and the least about the consumption stage. However, mostly positive information about environmental aspects were included in the analysed sustainability reports. Failures regarding sustainable development programmes were rarely mentioned.